Two new species of the Hypnoidini Schwarz, 1906 (Coleoptera: Elateridae: Dendrometrinae) from Afghanistan - Prosvirov, Alexander S. (Zootaxa, 2017)
Two new species of the tribe Hypnoidini Schwarz, 1906 are described from Afghanistan: Hypnoidus afghanus sp. nov. and Ligmargus kabakovi sp. nov. The genera Hypnoidus Dillwyn, 1829 and Ligmargus Stibick, 1976 as well as the tribe Hypnoidini are recorded for the first time in Afghanistan.